Zugehörigkeit und Rassismus: Orientierungen von Jugendlichen im Spiegel geographiedidaktischer Überlegungen - Schröder, Birte (transcript, 2019)
Where do I belong? The volume explores how young people negotiate affiliation and how to design a racism-critical education in relation to the world in which we live.